Draft genome sequence of a blaKPC-2-carrying citrobacter braakii isolate from Pediatric Hospital Wastewater in Peru - Salvatierra G. (2021)
Here, we report a draft genome sequence of a blaKPC-2-carrying Citrobacter braakii isolate from pediatric hospital effluent. Genome CF248 represents a multidrug-resistant C. braakii isolate derived from a clinical environment in Peru. Copyright © 2021 Salvatierra et al. This is an open-access article distributed under the terms of the Creative Commons Attribution 4.0 International license.